2021
DOI: 10.1002/ccd.29793
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐controlled intermittent coronary sinus occlusion improves the vasodilatory microvascular capacity and reduces myocardial injury in patients with STEMI

Abstract: Background: Preliminary data suggest that pressure-controlled intermittent coronary sinus occlusion (PICSO) might reduce the infarct size (IS) in patients with anterior STelevation myocardial infarction (STEMI). However, the applicability of this therapy to patients with inferior STEMI and its exact mechanism of action is uncertain.Methods and results: Thirty-six patients (27 anterior and 9 inferior) with STEMI underwent PICSO-assisted-primary percutaneous intervention (PPCI) and were compared with matched con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 21 publications
(66 reference statements)
0
13
0
Order By: Relevance
“…If the femoral artery route were established, IABP can be prepared simultaneously. Recently, STEMI DTU 30 was treated with left ventricular unloading 30 minutes before reperfusion, a significant improvement in the ratio of AAR to IS was observed; PiCSO therapy 31 may improve microvascular function and vasodilatory capacity, which contributes to reducing IS in patients with STEMI undergoing PPCI. PiCSO need 15-30 minutes for sheath preparation and cannulating the coronary sinus before coronary reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…If the femoral artery route were established, IABP can be prepared simultaneously. Recently, STEMI DTU 30 was treated with left ventricular unloading 30 minutes before reperfusion, a significant improvement in the ratio of AAR to IS was observed; PiCSO therapy 31 may improve microvascular function and vasodilatory capacity, which contributes to reducing IS in patients with STEMI undergoing PPCI. PiCSO need 15-30 minutes for sheath preparation and cannulating the coronary sinus before coronary reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary microvascular dysfunction in the STEACS setting is prognostically important (4,5,18), and its early and reliable identification during pPCI can guide stratification of adjunct therapies (24)(25)(26). Early work has shown that macroscopically red thrombi are associated with an adverse prognostic outcome (8, 9).…”
Section: Discussionmentioning
confidence: 99%
“…Egred et al (2020) obtained the important conclusion that patients who received PiCSO after reperfusion have a significantly smaller infarct size at 5 days and no procedural or device-related adverse effects [ 59 ]. A year later, Scarsini et al (2021) reached four key results in the PiCSO study: PiCSO immediately improved microvascular function after PCI in STEMI patients; PiCSO positively influenced coronary microcirculatory vasodilation; PiCSO-assisted PCI demonstrated a smaller infarct size at 6 months; PiCSO showed promising results in treating inferior STEMI [ 102 ]. …”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%
“…The effects of PiCSO in the heart reach a molecular level, by increasing relevant microRNA and transcription factors favoring cardiac regeneration by acting on cardiomyocytes and cardiac fibroblasts [ 60 ]. Further investigations are being conducted on PiCSO, yet there is still a lot to learn from this therapy; therefore, further investigation on this topic will be very beneficial ( Table 1 ) [ 58 , 59 , 60 , 102 ].…”
Section: Cardioprotective Devices That Unload the Heartmentioning
confidence: 99%